Knowledge, attitude and behavior towards the intention of farmers in applying food waste as fertilizers in Perak - Nurul Aida Yaacob (Tanjong Malim, 2023)
Knowledge, attitude and behavior towards the intention of farmers in applying food waste as fertilizers in Perak by Nurul Aida Yaacob